SUPERVISI AKADEMIK BERBASIS KEMITRAAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN GURU DI MAN 2 BANDUNG - Rinda Nurapriliani; Mulyawan Safwandy Nugraha (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of academic supervision in improving teachers’ instructional quality at MAN 2 Bandung, with a focus on supervision practices, teacher competency development processes, teaching performance indicators, implementation constraints, and strategies for enhancing supervision effectiveness. A qualitative approach with a case study design was employed in this research. Data were collected through interviews, observations, and documentation involving three informants, namely the vice principal for curriculum affairs and two teachers who had participated in academic supervision activities, conducted in April 2026. Data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that academic supervision was implemented in a humanistic, collaborative, and partnership-based manner through a structured cycle of pre-observation, classroom observation, post-observation, reflection, feedback, and follow-up. This process contributed to improvements in teachers’ lesson planning, instructional implementation, classroom management, use of learning technology, and formative assessment. The main challenges included limited time, heavy teaching workload, a limited number of supervisors, and teachers’ anxiety during observation, while improvement strategies were implemented through peer coaching, Subject Teacher Forum (MGMP), training programs, peer mentoring, digital supervision, and provision of learning facilities. The novelty of this study lies in strengthening a partnership-based academic supervision model that integrates evaluation and professional development functions in a collaborative manner within the madrasah context.